Lupenone Isolated from Diospyros melanoxylon Bark Non-competitively Inhibits alpha-amylase Activity - Mohan Krishna Durgam; Praveen Kumar Vemuri; Vijaya Lakshmi Bodiga; Sreedhar Bodiga (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Diabetes mellitus is a chronic disease that poses a serious global health problem, due to its associated effects on obesity and aging. Therapeutic strategies for targeting diabetes include the downregulation and/or inhibition of enzymes such as a-amylase and a-glucosidase, hydrolyzing the dietary carbohydrates in intestine. There is increasing interest for a-amylase inhibitors from natural sources. Our objective was to undertake the phytochemical screening of bark extracts of Diospyros melanoxylon for potential a-amylase inhibitory activity and further identification of the active principle and the underlying mechanisms of inhibition. Enzyme-assay guided fractionation of the Diospyros melanoxylon bark extract led to the isolation of a triterpene, Lupenone as a potential inhibitor of a-amylase, with a non-competitive inhibition and inhibitor constant = 30 mM. Lupenone-mediated inhibition of a-amylase responsible for the breakdown of dietary sugar may be effective in preventing postprandial hyperglycemia in the diabetic subjects.